Effects of high velocity oxy-fuel coatings on the tensile properties of S50C steel - M. Halmi, M. A.; Harimon, M. A.; Chue, D. (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC PVT. LTD.), 2020)
High-Velocity Oxy-Fuel (HVOF) coating is a thermal spray coating technique involving the carriage of coating powder into a flame mixture of oxygen and fuel ejected through a nozzle. The molten or semi-molten powder is propelled at high-velocity gas stream towards the surface to produce a strong and dense coating which enhances erosion resistance, wear resistance, and corrosion protection. However, the effect of the coating towards other mechanical properties such as tensile behaviour is uncertain. Therefore, this paper provides an assessment of the effect of HVOF coatings, coatings thickness and grit blasting on tensile behaviour of S50C steel. The tensile test was carried out according to the ASTM-E8/E8M standard and the tensile fracture surface was examined by using a Scanning Electron Microscope (SEM). Micro-hardness and grain size analysis was used to identify the different properties between coated and uncoated steels. Results showed that micro-hardness, yield- and tensile strength decreased due to the high-temperature effect of HVOF coating. Also, as the coating thickness increases, the yield- and tensile strength reduced because of the longer time-expose of the high temperature of the HVOF process. Besides that, grit blasting treatment lowered the yield- and tensile strength of the steel due to the embedment of the grit blasting. The fractographic analysis shows clear voids, spherical dimples and cleavage facets which indicate that both coated and uncoated steels underwent a “moderate” ductile fracture during the tensile loading.